Industrial structures and labour market outcomes : an examination of Poland in transition - Sibley, Christopher W. (Trinity College (Dublin, Ireland). Department of Economics, 2005)
This Thesis presents three papers. In our first paper we estimate the impact of transition on earnings inequality using data across Polish regions 1994-1997. Our central result is that earnings inequality is higher in regions that are more advanced in restructuring (higher labour productivity/job reallocation rates), controlling for unobservable regional fixed effects. At the national level rapid growth does not seem to be associated with earnings inequality. This aggregate relationship is shown to be misleading. The positive relationship between earnings inequality and the stage of transition across regions remains when we apply an infrastructure-deficit based instrumental variable approach to allow for reverse causality.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin